Integrated metabolomic and transcriptomic analyses reveal temporal dynamics of secondary metabolite accumulation in Cibotium barometz rhizome - Wang, Feng-Pan; Chen, Li-Jun; Zhou, Shao-Rong; Tang, Meng; Zhang, Xuejiao; Yan, Yue-Hong (Frontiers in Plant Science, 2025)
Cibotium barometz (Gou-ji) is a valued traditional Chinese medicinal herb with demonstrated efficacy in treating musculoskeletal and age-related conditions. The pharmacological properties of Gou-ji are closely associated with its phytochemical composition. However, a systematic understanding of the metabolic profile and its temporal dynamics in the rhizome—the primary medicinal part—remains limited. This study aimed to comprehensively characterize the secondary metabolite composition of C. barometz rhizome and elucidate its developmental regulation. Our specific objectives were to: (1) compare the metabolomic profiles of rhizomes at juvenile (YDS), intermediate (MDS), and mature (MS) stages; (2) investigate the transcriptomic basis underlying metabolite accumulation; and (3) quantify flavonoids across developmental stages. Using broadly targeted metabolomics, we identified a total of 761 secondary metabolites from Gou-ji, among which phenolic acids and flavonoids accounted for over 50%. Metabolite profiling revealed stage-specific shifts in accumulation patterns: phenolic acids were most enriched in YDS rhizome, alkaloids in MDS rhizome, and flavonoids in MS rhizome. In comparison with YDS or MDS rhizome, MS rhizome exhibited significant enrichment of numerous flavonoids, indicating a consistent and pronounced accumulation of flavonoids in more mature rhizome. Transcriptomic profiling further revealed upregulation of key genes involved in flavonoid biosynthesis pathways in MS rhizome, providing molecular insights into the observed metabolic changes. Furthermore, quantitative analysis confirmed higher flavonoid content in MS rhizome compared to YDS, particularly for the high-abundance flavonoids: (-)-epicatechin, apigenin-7-glucoside, naringenin-7-glucoside, vitexin, apigenin, (-)-catechin, eriodictyol, and naringenin chalcone. It supported the potential role of prolonged growth in enhancing flavonoid accumulation. These findings not only enhance our understanding of the phytochemical basis of Gou-ji’s medicinal efficacy but also offer valuable insights for quality assessment and optimized harvesting of this traditional herb.